THE STRUGGLE OF IDEOLOGY IN THE SPIRITUALITY OF BALINESE SOCIETY IN THE MIDDLE AGE: A CRITICAL DISCOURSE ANALYSIS - I Wayan Gede Wisnu; I Wayan Cika; A.A. Ngurah Anom Kumbara; Ni Made Wiasti (E-Journal of Cultural Studies, 2023)
This paper is a description of the ideological struggle in the spirituality of Balinese society in the middle Bali Period which was articulated through discourse as a discursive. The choice of such a topic departs from a perception of the typology of Balinese society which is assumed to have spiritual stability, but instead experiences ideological struggles in this realm as indicated by the phenomenon of the middle Bali period. The phenomenon of spirituality is elaborated as a problem which includes the form and the implications of ideological struggles in the spirituality of the Balinese people of the Middle Bali Period. The explanation of the variables in this paper uses critical discourse theory which refers to Foucault's view. The results of the study reveal that the forms of the spirituality of Balinese society in the middle Bali Period include strengtheningteachings of Shiva and strengthening the Shiva-Buddhist concept. Meanwhile, the implications of the struggle include appreciation of the authority of Shiva Sidhanta's teachings and degradation of cognition of "Shiva Bhujangga" teachings. Keywords: the struggle of ideology, spirituality, Balinese society, and the Middle Bali Period